The challenges and benefits of a genuine partnership between Music Therapy and Neuroscience: a dialog between scientist and therapist - Magee, Wendy L.; Stewart, Lauren (Frontiers in Human Neuroscience, 2015)
Collaborations between neuroscience and music therapy promise many mutual benefits given the different knowledge bases, experiences and specialist skills possessed by each discipline. Primarily, music therapists deliver music-based interventions on a daily basis with numerous populations; neuroscientists measure clinical changes in ways that provide an evidence base for progressing clinical care. Although recent developments suggest that partnerships between the two can produce positive outcomes for both fields, these collaborations are not considered mainstream. The following dialog between an experienced professional from each discipline explores the potential for collaboration, as well as the misconceptions that may be preventing further synergies from developing.